2007
DOI: 10.1007/s10995-006-0152-5
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Time in the U.S. on the Duration of Breastfeeding in Women of Mexican Descent

Abstract: Objectives-Although women of Mexican decent have high rates of breastfeeding, these rates may vary considerably by acculturation level. This study investigated whether increased years of residence in the U.S. is associated with poorer breastfeeding practices, including shorter duration of any and exclusive breastfeeding, in a population of low-income mothers of Mexican descent. (n=490) were recruited from prenatal clinics serving a predominantly Mexican-origin population in an agricultural region of California… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 16 publications
7
56
4
Order By: Relevance
“…These findings are consistent with evidence from several studies documenting Latinas preference nonexclusive breastfeeding or formula feeding. [8][9][10][11][12][13][32][33][34][35] However, our rates of exclusive breastfeeding were lower than those reported in the literature, [36] as nearly none of breastfeeding infants were receiving breast milk exclusively. The one exclusive breastfed infant belonged in the overweight group and further analysis of this infant"s dietary intake revealed the mother reported frequently breastfeeding as often as 20 times during a 24-hour period.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…These findings are consistent with evidence from several studies documenting Latinas preference nonexclusive breastfeeding or formula feeding. [8][9][10][11][12][13][32][33][34][35] However, our rates of exclusive breastfeeding were lower than those reported in the literature, [36] as nearly none of breastfeeding infants were receiving breast milk exclusively. The one exclusive breastfed infant belonged in the overweight group and further analysis of this infant"s dietary intake revealed the mother reported frequently breastfeeding as often as 20 times during a 24-hour period.…”
Section: Discussioncontrasting
confidence: 79%
“…[6] Hispanic mothers display positive attitudes toward breastfeeding initiation but commonly supplement breast milk with formula feeding beginning early in infancy. [7,8] Favorable beliefs about combining breast milk and formula feeding may contribute to very low rates of exclusive breastfeeding. [9][10][11] Many Latina mothers recognize the importance and benefits of breastfeeding, but often provide complimentary formula feeding for fear of their ability to keep their infants sated and well-nourished.…”
Section: Introductionmentioning
confidence: 99%
“…Modernization implies acculturation or adoption of the values, beliefs and behaviours of the mainstream society (43) . Acculturation studies show that individuals vary in the levels to which they maintain their original culture and adopt the practices of their new environment (41)(42)(43)(44)(45)(46) . In a study conducted among low-income Latinas in the USA (44) , a multidimensional assessment of acculturation showed that the best breast-feeding outcomes were observed in a low-integrated group, which scored low on both the Hispanic and the American scales, followed by the group of traditional Hispanics.…”
Section: Discussionmentioning
confidence: 99%
“…Forste 19 and Liu 20 reported the low interest in BF in black women compared to non-black women and Jevi 21 was seen the BFD in black women less than in white women and Spanish women in USA. Several studies 22,23 approved the infl uence of immigra on on BFD. BFD varia on among ethnic groups in present study probably related to diff erences in health, nutri on and socio-demographic factors that should be studied in a comprehensive survey in future.…”
Section: Discussionmentioning
confidence: 99%